Influencing parameters on measurement accuracy in dynamic mechanical analysis of thermoplastic polymers and their composites. (November 2020) - Schalnat, Joanna; Gómez, David Garoz; Daelemans, Lode; De Baere, Ives; De Clerck, Karen; Van Paepegem, Wim
Abstract: Long-term predictions of material properties such as stiffness and creep resistance are important in many engineering applications and require high reliability and accuracy. This is especially true for polymer materials and their composites as their viscoelastic nature results in time-dependent material behaviour and any measurement uncertainties or errors amplify in long-term predictions. To measure this behaviour at smallest loadings, Dynamic Mechanical Analysis (DMA) is frequently declared as an ideal method. However, the measurement accuracy and repeatability of this method is strongly influenced by (i) the testing fixture and corresponding loading mode, (ii) the sample preparation and (iii) the plotting scale to interpret the test results. In this study, relevant experimental parameters were found for DMA and a proper procedure was designed, which was then applied to measure the viscoelastic behaviour of a highly temperature and creep resistant thermoplastic polymer (polyethersulfone) and of a highly graphite filled polypropylene composite. In combination with finite element simulations and in-situ strain measurements by digital image correlation (DIC), the main influences on measurement accuracy of three-point-bending DMA were identified and subsequently used to determine measurement guidelines. Using these guidelines, DMA measurements allow quantitative determination of the viscoelastic response for rigid polymer and composite materials. Highlights: Accuracy of DMA can greatly be improved by a cautious testing procedure. The limitations in frequency and amplitude should not be set generically, but should be tailored to the material and setup. Sample dimensions and their precision are crucial for the repeatability of the DMA test. More repetitions are required for a quantitative result. The first cycle in a DMA measurement is less stable than the following.